Anatomy of an incident - Sachto, Ayelet; Walcer, Adrienne; Yang, Jessie (O'Reilly Media, Inc., 2022)
When it comes to system design, failure is inevitable. Scientists and engineers implement solutions based on the available information, without a complete knowledge of the future. You can't always anticipate the next zero-day event, viral media trend, weather disaster, or shift in technology. But you can be prepared to respond when incidents like these affect your systems. With this report, SRE and DevOps practitioners, IT managers, and engineering leaders will explore methods to help their organizations prepare for, respond to, and recover from incidents. With advice from Ayelet Sachto, Adrienne Walcer, and Jessie Yang, you'll learn how to prepare for and handle failure if and when it happens.